Report on industrial attachment with Pratt & Whitney Services Pte Ltd - Tay, Ken. (2011)
This report aims to cover the projects carried out by the author during his 22 week Industrial Attachment at Pratt & Whitney Services. The author was part of the Rotating Air Seal repair development team. He assisted in the Repair Process Launch Review preparation, which entails evaluating technical data, identifying critical to quality key product characteristics, evaulating capital requirements, identification of tooling requirements and creating summary of operations.